Bladder carcinosarcoma: a case observation - Maestroni, U.; Giollo, A.; Barbieri, et al., A. (Acta Biomedica Atenei Parmensis, 2004)
Carcinosarcoma of the bladder is a very unusual neoplasm that arises more frequently in males with a greater incidence in the seventh decade of life. There are no patognomonic clinical findings or symptoms to address its presence. Symptoms, as for other bladder cancers, are fundamentally represented by haematuria and dysuria. It has a very aggressive clinical behaviour and it is histologically characterized by a malignant epithelial component associated with a sarcoma-like (sarcomatoid) component variably represented.